Family migration: a vehicle of child morbidity in the informal settlements of Nairobi City, Kenya? - Adama Konseiga (Institute for the Study of Labor (IZA), 2008)
Parental migration is often found to be negatively correlated with child health in Africa, yet the causal mechanisms are poorly understood. The paper uses a dataset that provides information from the respondent parent on child morbidity both in the rural and urban settings. Households first endogenously determine whether they will gain from participating in migration and, if they do, whether they will leave the children behind or not. The final choice is made to ensure the optimal survival chances for the child. This paper contributes to understanding the health consequences of raising the children in the context of increasing urban poverty in Nairobi, Kenya. The findings indicate that households who migrated together with their children in the slums of Nairobi experience higher child morbidity (43 per cent have at least one sick child in the last one month) as compared to households who leave children in their upcountry homes (31 per cent of morbidity rate). Even though children of migrants are safer upcountry, not all households can afford this strategy. Households are able to choose this strategy only if they have a strong social support network in their origin community and/or they are big size households. This is an important finding in targeting the Millennium Development Goals.
urn:nbn:de:101:1-2008070228
Keywords: C31; 360; Childhood morbidity; split migration; incidental truncation; informal settlements; Nairobi; Kenya; Kindersterblichkeit; Eltern; Binnenwanderung; Landflucht; Slum; Kenia; Nairobi